Puerperas’ knowledge regarding postpartum exercises in a tertiary hospital in the Capricorn District of Limpopo Province South Africa - M Mbombi; M K Thopola; J C Kgole (South African Medical Association, 2017)
Background. Postpartum exercises (PPEs) are critical for the involution process post delivery. PPE affects the physical and psychological wellbeing of puerperas. Clinical observation shows a lack of exercise by puerperas in postnatal units.Objectives. To determine puerperas’ knowledge regarding PPE, as well as to develop a health education programme on PPE.Methods. A quantitative, non-experimental, descriptive research design was employed. Probability random sampling was used to ensure that all puerperas had an equal opportunity to be selected. The sample comprised 50 puerperas who were admitted to a postnatal unit at a tertiary hospital in the Capricorn District, Limpopo, South Africa. The researchers distributed questionnaires that contained closedended questions to the puerperas on the days they visited the institution. Reviews of the literature and consultations with midwifery experts were conducted to ensure content validity. Data analysis was done through descriptive statistics.Results. Our data revealed that 68% of puerperas participating in the study lacked knowledge regarding PPE, whereas 72% of puerperas were not exercising due to perineal pains, discomfort, exhaustion and a lack of educational programmes at clinics and hospitals. The study showed that there was a high rate of ignorance among puerperas regarding the importance of PPE.Conclusion. We recommend that registered midwives initiate, develop and implement a sustainable educational programme on PPE in postnatal units.